THE ASPECT OF CONFLICT BETWEEN PATERNALISM AND CONSTITUTIONALISM IN KOREAN CONTEMPORARY SOCIETY - OH, Kyong-geun (International Journal of Korean Humanities and Social Sciences, 2019)
As of the 21st century, Koreans are struggling to achieve an advanced society. Material abundance may be a prerequisite for advanced society, but what is more important and essential is transparent and just society implementation in which an equal opportunity is given to all members of society and fair competition is ensured by fair rules. Unfortunately, in the Korean society, almost in all the layers of it, corruption and injustice/ immorality are still rampant. I believe that such a phenomenon comes from the weak sense of the rule of law in Korean society compared with the other developed countries. Therefore, this paper considers the structure of consciousness of Koreans, which makes such things possible and makes it harder to eradicate, centered on Confucianism which emphasizes humanism or paternalism rather than the rule of law, and the mindset/ consciousness of Korean shamanism which does not actively try to fight against evil.